The Correlation between Interleukin-10 Serum with Bacterial Index in Multidrug Therapy-treated Leprosy Patients - Eva Krishna Sutedja; Jono Hadi Agusni; Hartati Purbo Dharmadji (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Immune respons disturbance oftenly found in leprosy patient, mainly in various T cell subset and cytokine immune system arranger. Interleukin-10 produced by Th 2 cell, Th3 cell, monocyte, dendritic cell, eosinophil, mast cell, and keratinocyte. Interleukin 10 (IL-10) works in active macrophage to end the respons to microbe and restore the system to the resting state after the microbes are destroyed. Purpose: To analyze correlation between IL-10 level with Bacterial Index (BI)  in Multidrug Therapy (MDT)-treared leprosy patient. Methods: Cross sectional analytical observational study of 43 subjects, consisting of 38 males (88.4%) and 5 females (11.6%). The IL-10 examination used quantitative sandwich enzyme immunoassay, human IL-10 Quantikine® ELISA methods from R & D systems® Result: There was positive correlation between IL-10 and BI of MDT-treated leprosy patient (r = 0,504; p=0,001). Conclusion: The increasing of IL-0 correlated with high BI. Interleukin-10 level is higher in MB type than PB type of leprosy patients.Key words: Interleukin-10 (IL-10), bacterial index (BI).